2008
DOI: 10.1038/onc.2008.104
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 promotes cell proliferation and survival via phosphorylation and inhibition of FOXO1 transcription factor

Abstract: The forkhead box O (FOXO) transcription factor FOXO1 functions as a tumor suppressor by regulating expression of genes involved in apoptosis, cell cycle arrest and oxidative detoxification. Here, we demonstrate that cyclin-dependent kinase 1 (CDK1) specifically phosphorylates FOXO1 at serine 249 (S249) in vitro and in vivo. Coimmunoprecipitation assays demonstrate that both endogenous CDK1 and ectopically expressed CDK1 form a protein complex with FOXO1 in prostate cancer (PCa) cells. In vitro protein binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 56 publications
1
107
0
Order By: Relevance
“…CDK2 (47) and, more recently, CDK1 (48,49) were reported to regulate FOXO1 by phosphorylation on S249, which is unaltered in our phosphosite mutant. CDK2 phosphorylation on S249 leads to cytoplasmic localization and decreased activity in both wild-type and FOXO1;AAA in a p53-independent fashion as measured by target gene expression (47).…”
Section: Discussionmentioning
confidence: 95%
“…CDK2 (47) and, more recently, CDK1 (48,49) were reported to regulate FOXO1 by phosphorylation on S249, which is unaltered in our phosphosite mutant. CDK2 phosphorylation on S249 leads to cytoplasmic localization and decreased activity in both wild-type and FOXO1;AAA in a p53-independent fashion as measured by target gene expression (47).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that FOXO1 function was closely related with its phosphorylation and acetylation modification which determined its transcriptional activity (40)(41)(42)(43)(44). Recent studies found that microRNAs, such as miR-96 and miR-370, downregulated FOXO1 expression (28,29).…”
Section: Discussionmentioning
confidence: 97%
“…Research has demonstrated that, in prostate cancer cells, CDK1 phosphorylates FOXO1 at Ser249, thereby, inhibiting the transcriptional activity of FOXO1 and reducing the effects of FOXO1 on mitosis. FOXO1 phosphorylation induced by CDK1 not only eliminates the effect of FOXO1 on cell death, but also reduces the inhibitory effects of FOXO1 on the proliferation of malignant transformed cells (53). In addition to CDK1 and CDK2, a recent study suggested that the CDK5 can influence the transcriptional activity of FOXO1 directly.…”
Section: Cyclin-dependent Kinases (Cdks)mentioning
confidence: 99%